Patients with first recurrent retroperitoneal sarcoma that can be macroscopically completely resected can achieve comparable outcomes with that of primary patients after en bloc resection of tumor and adjacent organs - Wang, Zhen; Wu, Jian-hui; Li, Cheng-peng; Lv, Ang; Qiu, Hui; Tian, Xiu-yun; Liu, Bo-nan; Hao, Chun-yi (Frontiers in Surgery, 2022)
The outcomes of patients with primary retroperitoneal sarcoma (RPS) are significantly superior to those with recurrence. En bloc resection of tumor and adjacent organs is recommended in primary RPS. However, whether en bloc resection of tumor and adjacent organs can benefit recurrent patients or some recurrent patients is unclear. We compared the outcomes of patients with primary RPS, first recurrence (RPS-Rec1), and ≥2 recurrences (≥RPS-Rec2) to evaluate the value and criteria for en bloc resection of tumor and adjacent organs in recurrent cases. We evaluated the safety of en bloc resection of tumor and adjacent organs by assessing operation time, blood loss volume, postoperative morbidities (POM), and efficacy by comparing local recurrence and peritoneal metastasis (LR-PM), distant metastasis, progression-free survival (PFS), and overall survival (OS). A total of 101, 47, and 30 patients with primary RPS, RPS-Rec1, and ≥RPS-Rec2 were included, respectively. Recurrent RPS invaded more adjacent organs and surrounding fat tissue than primary RPS. The operation time, amount of blood loss, incidence of grade III–V POM, LR-PM rate, PFS, and OS in the RPS-Rec1 group were similar to those of the primary group, both of which were significantly superior to those of the ≥RPS-Rec2 group. Macroscopically incomplete resection and high-grade RPS rather than first recurrence were independent risk factors for LR-PM, PFS, and OS. In conclusion, the safety and efficacy of en bloc resection of tumor and adjacent organs in RPS-Rec1 were comparable with those in primary RPS but significantly superior to those of ≥RPS-Rec2. For RPS-Rec1, comparable outcomes can be achieved in patients with primary RPS, especially those who can achieved macroscopically complete resection.